2016
DOI: 10.1016/j.jcf.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Microbial colonization and lung function in adolescents with cystic fibrosis

Abstract: With intensified antibiotic therapy and longer survival, patients with cystic fibrosis (CF) are colonized with a more complex pattern of bacteria and fungi. However, the clinical relevance of these emerging pathogens for lung function remains poorly defined. The aim of this study was to assess the association of bacterial and fungal colonization patterns with lung function in adolescent patients with CF. Microbial colonization patterns and lung function parameters were assessed in 770 adolescent European (Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…This is the first time this has been reported. In a recent longitudinal study the sputum microbiology and clinical outcomes of 770 adolescents with CF were recorded and AF was the only species that was associated with an increased risk for infection with PA [28]. This highlights the importance of monitoring the co-colonisation status of CF patients.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is the first time this has been reported. In a recent longitudinal study the sputum microbiology and clinical outcomes of 770 adolescents with CF were recorded and AF was the only species that was associated with an increased risk for infection with PA [28]. This highlights the importance of monitoring the co-colonisation status of CF patients.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Once fungi are isolated from the lung, the next question that follows is whether these microbes are contaminants, transiently recovered, colonizers, or pathogens. The clinical outcomes related to presence of bacteria in the CF lung may be either protective or deleterious, and this understanding has influenced thinking about the isolation of fungi . Definitions for Aspergillus colonization and infection have been proposed, though there remain no standardized definitions.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…C albicans , the most common species isolated, is generally thought of as non‐pathogenic. This being said, when identified as a colonizer of the CF airway C albicans is associated with increased rates of decline in FEV 1 in some studies; while an association with preserved lung function was found in another study …”
Section: Clinical Diagnosismentioning
confidence: 99%
“…CF patients are frequently colonized with P. aeruginosa (Hector et al, 2016) and, like COPD patients, are prone to develop exacerbations upon viral infection. Chattoraj et al (2011a) showed decreased production of type I and III IFNs in CF cells exposed to P. aeruginosa and HRV compared with cells exposed to HRV alone.…”
Section: Bacterial Pathogens Influencing the Response To Viral Infectionmentioning
confidence: 99%